PENENTUAN HARGA AIR IRIGASI PADA DAERAH IRIGASI LINTAS KABUPATEN, DAS NGASINAN – NGROWO KABUPATEN TULUNGAGUNG DAN TRENGGALEK - Dian Noorvy Kh; Suhudi Suhudi (BUANA SAINS, 2009)
This study represent study pricing of relied on water potency of each irrigation area in DAS Ngasinan - Ngrowo Sub-Province of Tulungagung and of Trenggalek and also willingness and ability to local farmer and verification to field. Drainage basin pass by quickly sub-province have problems of complex from between farmer alone till institute and its facilities and basic facilities. Role and also and society of commitment institute each proving its commitment to management of water resource obtained to be data to be done by collecting primary and secondary data, including in it by interview. Data Sample taken by maximum from 2 - 3% from farmer family population/irrigation area with assumption each farmer have 0,5 ha rice field. Execution of gathering of sample that is with examination of method statistic of proportional sampling random to see how far taken sample fulfill examination to be done. Beside that in this study even also, studied till make a guidance of price pixing irrigate to area of around him with have directive to factors having an effect on in price pixing sell this water. Price sell water determined by lessening Value Sell Agro Product with production cost, operating expenses and conservancy, expense of investment, requirement of farmer life and farming remains, and later divided with amount of water required/ha. Price pixing irrigate this give contribution that expecting of farmer can become self-supporting farmer by making it one of the consideration of farmer to participate in defrayal of Operation and Conservancy of Network irrigation